CanDIG: Federated network across Canada for multi-omic and health data discovery and analysis - L. Jonathan Dursi; Zoltan Bozoky; Richard de Borja; Haoyuan Li; David Bujold; Adam Lipski; Shaikh Farhan Rashid; Amanjeev Sethi; Neelam Memon; Dashaylan Naidoo; Felipe Coral-Sasso; Matthew Wong; et al. (Elsevier, 2021)
We present the Canadian Distributed Infrastructure for Genomics (CanDIG) platform, which enables federated querying and analysis of human genomics and linked biomedical data. CanDIG leverages the standards and frameworks of the Global Alliance for Genomics and Health (GA4GH) and currently hosts data for five pan-Canadian projects. We describe CanDIG's key design decisions and features as a guide for other federated data systems.